2006
DOI: 10.1029/2005ja011403
|View full text |Cite
|
Sign up to set email alerts
|

Fate of outflowing suprathermal oxygen ions that originate in the polar ionosphere

Abstract: [1] We investigate the transport and ultimate fate of outflowing suprathermal O + ions by kinetic means using a full-particle tracing scheme. We launched O + ions in order to determine their final destination in terms of the magnetopause, the distant tail, the ring current (L-shell of 5), and the atmosphere. The number of O + ions that reached each of the destinations was calculated quantitatively by employing an empirical model of the outflowing ion distribution. This empirical model is based on long-term dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 60 publications
4
81
0
Order By: Relevance
“…The acceleration of ionospheric ions and their transport into the plasma sheet and ring current have been investigated by particle tracing calculations for a number of years (Green and Horwitz 1986;Sauvaud and Delcourt 1987;Delcourt et al 1989Delcourt et al , 1990Cladis and Francis 1992;Peroomian 1994;Peroomian andAshour-Abdalla 1995, 1996;Moore and Delcourt 1995;Ebihara et al 2006;Yau et al 2012). More recently, Peroomian et al (2006Peroomian et al ( , 2007Peroomian et al ( , 2011aPeroomian et al ( , 2011b have investigated the access and energization of ionospheric ions to the magnetotail during geomagnetic storms by using LSK particle tracing simulation using time-dependent electric and magnetic fields of individual storm events.…”
Section: Simulating the Ion Historymentioning
confidence: 99%
“…The acceleration of ionospheric ions and their transport into the plasma sheet and ring current have been investigated by particle tracing calculations for a number of years (Green and Horwitz 1986;Sauvaud and Delcourt 1987;Delcourt et al 1989Delcourt et al , 1990Cladis and Francis 1992;Peroomian 1994;Peroomian andAshour-Abdalla 1995, 1996;Moore and Delcourt 1995;Ebihara et al 2006;Yau et al 2012). More recently, Peroomian et al (2006Peroomian et al ( , 2007Peroomian et al ( , 2011aPeroomian et al ( , 2011b have investigated the access and energization of ionospheric ions to the magnetotail during geomagnetic storms by using LSK particle tracing simulation using time-dependent electric and magnetic fields of individual storm events.…”
Section: Simulating the Ion Historymentioning
confidence: 99%
“…High altitude measurements such as those we present in this paper does not directly deal with this controversy regarding the total outflow, as all observed particles have reached escape energy. Our interest lies in the further energization of escaping particles, and their role in the global circulation of mass and energy in the magnetospheric system (Winglee et al, 2002;Winglee, 2004) as well as the final fate of these ions (Ebihara et al, 2006). Delcourt (1994) found that centrifugal effects could be important near the frontside magnetopause.…”
Section: Introductionmentioning
confidence: 99%
“…Their fate, however, is not certain. It has been argued that the final destination of these ions depends on the ratio of their velocity parallel to the magnetic field and the convection velocity perpendicular to the magnetic field (Ebihara et al, 2006;Haaland et al, 2012;Li et al, 2013), particularly during periods of southward IMF. Haaland et al (2012) estimated that 90 % of the ions flowing into the lobes are convected into the plasma sheet.…”
Section: Introductionmentioning
confidence: 99%